A hipertensão arterial na diabetes mellitus etiopatogenia e tratamento. - I Menezes (Acta Médica Portuguesa, 1989)
The different aspects of the etiopathogenesis of arterial hypertension in diabetes mellitus are reviewed. Therapeutic approaches and the several phases of treatment are discussed, with particular emphasis on the most recent developments.